2019
DOI: 10.3390/polym11071138
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Compression, and Buffering Performance of Pomelo-Like Hierarchical Capsules Containing Shear Thickening Fluid

Abstract: In this study, a double-walled and pomelo-like hierarchical shear thickening fluid (STF) is successfully encapsulated using the simple and environment-friendly calcium alginate encapsulation technique by instilling STF into sodium alginate (SA) and crosslinking by calcium chloride solution. The encapsulated STF has a pomelo-like structure with a shell thickness of 2.9 μm and core pores with a size of 21.43 μm. The effect of the size of STF capsules (2.10, 1.89, 1.86, 1.83, 1.73, and 1.63 mm) is explored in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In contrast, this absorption rate was significantly higher than that reported in previous studies involving the use of expanded vermiculite, 54 SEBS-g-MAH, 55 fibers, 56 shear thickening solution, 57 spacer fabrics, 39 D3O-filled PU foams, 58 and teak-mimicking biofoam composites. 40 Overall, the cushioning composites prepared in this study possess the advantages of low-cost and high-energy absorption efficiency. Moreover, they overcome the limitations associated with single-structure foam, such as poor mechanical strength, low elasticity, and limited energy absorption capability.…”
Section: Thermal Performancementioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, this absorption rate was significantly higher than that reported in previous studies involving the use of expanded vermiculite, 54 SEBS-g-MAH, 55 fibers, 56 shear thickening solution, 57 spacer fabrics, 39 D3O-filled PU foams, 58 and teak-mimicking biofoam composites. 40 Overall, the cushioning composites prepared in this study possess the advantages of low-cost and high-energy absorption efficiency. Moreover, they overcome the limitations associated with single-structure foam, such as poor mechanical strength, low elasticity, and limited energy absorption capability.…”
Section: Thermal Performancementioning
confidence: 82%
“…In order to address the limited reusability of conventional PU foam, our research team developed a composite structure by combining fabric with PU foam. 35,[40][41][42] We discovered that the fabric reinforcement significantly enhanced the overall strength and elasticity of the foam composite. Through our investigation, we determined that a hexagonal warp-knit fabric structure with a side length and wall thickness of 1 cm exhibited the best cushioning performance.…”
Section: Introductionmentioning
confidence: 98%
“…Bennacef et al and Li et al (2019). These studies describe methods, which produce capsules ranging from 500 μm to 1 mm in size.…”
Section: Study Of Geometrical Parameters Of Capsulesmentioning
confidence: 99%
“…Only when the two ingredients are mixed, a stable shear thickening system with low initial viscosity can be formed. [16][17][18] Shenoy and Wagner added a small amount of PEG with different relative molecular weight (MW = 4000, 6000, and 10,000) to STF with PEG (MW = 400) as the dispersion medium. Through rheological property test, it was found that the shear thickening behavior of STF increased with the relative molecular weight and content of PEG.…”
Section: Introductionmentioning
confidence: 99%